EVALUASI KURIKULUM PENDIDIKAN AGAMA ISLAM DI TENGAH DINAMIKA POLITIK PENDIDIKAN DI INDONESIA - Shelly Alvareza Zazkia; Tasman Hamami (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2021)
The curriculum in Indonesia often changes from time to time, but the results of these changes have not been optimal and are still far from being expected. The research objective is to reveal the various constraints or problems that have occurred during curriculum changes from the Old Order era to the reform era. Various obstacles that were found were the lack of professionalism of teachers in facing curriculum changes, a lack of reference books, and there were still many teachers who had different understandings of Curriculum-13 and experienced confusion in grasping the concept, substance, and mechanism of implementing Curriculum of 2013 Education Unit Level Curriculum. The results of the evaluation obtained were the importance of socialization and conducting teaching training before implementing the curriculum in formal teaching-learning process activities, then the government always paid attention to reference books that were used by teachers and students because every curriculum change was also followed (in addition to the method) of the material used. changed (update). So with that teachers and students can carry out the contents of the curriculum properly and following the objectives to be achieved.